2010
DOI: 10.1096/fj.09-150045
|View full text |Cite
|
Sign up to set email alerts
|

MAP kinase phosphatase‐1 deficiency impairs skeletal muscle regeneration and exacerbates muscular dystrophy

Abstract: In skeletal muscle, the mitogen-activated protein kinase (MAPK) phosphatase-1 (MKP-1) is a critical negative regulator of the MAPKs. Since the MAPKs have been reported to be both positive and negative for myogenesis, the physiological role of MKP-1 in skeletal muscle repair and regeneration has remained unclear. Here, we show that MKP-1 plays an essential role in adult regenerative myogenesis. In a cardiotoxin-induced muscle injury model, lack of MKP-1 impaired muscle regeneration. In mdx mice, MKP-1 deficienc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
71
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(75 citation statements)
references
References 41 publications
3
71
1
Order By: Relevance
“…Satellite cell-intrinsic MKP-1 loss neither affected activation of p38 (a critical regulatory pathway in satellite cell behavior) or myogenesis in any of the models, whereas dysregulated cytokine production in macrophages lacking MKP-1 / altered satellite cell functions in a paracrine manner. Interestingly, previous studies had anticipated a relevant function for MKP-1 in myogenesis (Bennett and Tonks, 1997;Wu et al, 2006;Roth et al, 2009;Shi et al, 2010). The distinct findings concerning myogenesis could be explained by the different experimental models used, supporting the need for a future evaluation of MKP-1 function using muscle-specific deletion approaches.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Satellite cell-intrinsic MKP-1 loss neither affected activation of p38 (a critical regulatory pathway in satellite cell behavior) or myogenesis in any of the models, whereas dysregulated cytokine production in macrophages lacking MKP-1 / altered satellite cell functions in a paracrine manner. Interestingly, previous studies had anticipated a relevant function for MKP-1 in myogenesis (Bennett and Tonks, 1997;Wu et al, 2006;Roth et al, 2009;Shi et al, 2010). The distinct findings concerning myogenesis could be explained by the different experimental models used, supporting the need for a future evaluation of MKP-1 function using muscle-specific deletion approaches.…”
Section: Discussionmentioning
confidence: 91%
“…gain-and loss-of-function studies in vitro and in vivo (Bennett and Tonks, 1997;Wu et al, 2006;Roth et al, 2009;Shi et al, 2010). Similarly, increases in TNF, IL-6 (interleukin-6), and IL-10 (interleukin-10) expression dependent on p38 activation, concomitant with enhanced induced NO synthase-NO and reduced arginase synthesis, have been proposed to underlie the exacerbated response to endotoxin challenge in mice genetically deficient in MKP-1 (Chi et al, 2006;Hammer et al, 2006;Wu et al, 2006;Zhao et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Although a wide body of evidence supports the pro-myogenic role of p38 MAPK, several reports also imply the involvement of p38 MAPK in muscle cell proliferation. The concomitant activation of p38 MAPKα/ and satellite cells imply that p38 MAPK may also be involved in satellite cell activation, since blockade of p38 MAPK by pharmacological inhibitors of p38 MAPK prevents both satellite cell proliferation and differentiation (Jones et al, 2005;Shi et al, 2010). A recent study using p38 -deficient mice revealed that muscles lacking this isoform of p38 MAPK contain 50% less satellite cells, and these cells exhibit reduced proliferation (Gillespie et al, 2009) implying that this p38 MAPK isoform may also be an important regulator of satellite cell deposition and proliferation.…”
Section: Wwwintechopencommentioning
confidence: 99%
“…Hence, MKP-1 plays both positive and negative roles in myogenesis in a temporal manner by selectively regulating one or more MAPKs (Figure 1). MKP-1 appears to be directly coupled to the myogenic transcriptional machinery as studies have shown that MKP-1 is a target for upregulation by MyoD (Shi et al, 2010). Within the proximal promoter of MKP-1 there resides an E-box binding site that serves to mediate MKP-1 activation by MyoD (Shi et al, 2010).…”
Section: Mkps In Skeletal Myogenesis and Skeletal Muscle Functionmentioning
confidence: 99%
“…MKP-1 is a nuclear phosphatase that dephosphrylates p38 MAPK, JNK, and ERK1/2 not only in skeletal muscle but also in the immune, metabolic, and nervous system as well [9,[31][32][33][34]. In the cardiotoxin-induced skeletal muscle regeneration, knockout of MKP-1 impaired the recovery of the damaged muscle likely through the effect of p38 MAPK pathways on muscle stem cell function [33], since the precocious differentiation of muscle stem cells caused by enhanced p38 MAPK may slow down the injured muscle from returning to a normal musculature [33]. Interestingly, when another MKP family member MKP-5 was knocked out, muscle regeneration following damage was greatly improved [35].…”
mentioning
confidence: 99%